2010
DOI: 10.1159/000236024
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth-Based First-Line Therapy for <i>Helicobacter pylori</i> Eradication in Type 2 Diabetes Mellitus Patients

Abstract: Background/Aim: The primary aim of this study was to assess the efficacy of a bismuth-based quadruple regimen as first-line therapy for Helicobacter pylori (HP) eradication in diabetes mellitus (DM) patients. The secondary aim was to study the effect of HP eradication on dyspeptic symptoms in DM patients. Method: Eighty-nine consecutive type 2 DM and 48 non-diabetic age- and sex-matched patients were enrolled in this study. Diabetic patients were randomized to receive either pantoprazole (40 mg b.i.d.), clarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…9,21,22 Studies for the effect of type 2 diabetes on the eradication rate of H. pylori treatment are limited, 2,8,9,2325 but they showed similar results of lower eradication rate compared to non-diabetic controls with standard triple antibiotics for 7–14 days, except one study showing similar eradication rate between two groups treated with bismuth-based quadruple regimen for 14 days. 26 Recently, one retrospective study reported similar eradication rate between type 2 diabetic patients and non-diabetic subjects with standard triple antibiotics for 7–14 days. 27 The proposed mechanism of lower eradication rate in diabetic patients is impaired gastric mucosal microvasculature leading to reduced antibiotics absorption, frequent antibiotic usage in diabetic patient group due to recurrent bacterial infections, and immunosuppressive condition of diabetes.…”
Section: Discussionmentioning
confidence: 95%
“…9,21,22 Studies for the effect of type 2 diabetes on the eradication rate of H. pylori treatment are limited, 2,8,9,2325 but they showed similar results of lower eradication rate compared to non-diabetic controls with standard triple antibiotics for 7–14 days, except one study showing similar eradication rate between two groups treated with bismuth-based quadruple regimen for 14 days. 26 Recently, one retrospective study reported similar eradication rate between type 2 diabetic patients and non-diabetic subjects with standard triple antibiotics for 7–14 days. 27 The proposed mechanism of lower eradication rate in diabetic patients is impaired gastric mucosal microvasculature leading to reduced antibiotics absorption, frequent antibiotic usage in diabetic patient group due to recurrent bacterial infections, and immunosuppressive condition of diabetes.…”
Section: Discussionmentioning
confidence: 95%
“…In the study by Demir et al [21] of 89 type 2 diabetic patients, the eradication rate was 51% with standard triple therapy (PPI, clarithromycin and amoxicillin) and this could be increased by a quadruple regimen (pantoprazole, bismuth, tetracycline and metronidazole) to 85%. The eradication rate was significantly lower in the DM group than in the non-DM group.…”
Section: Discussionmentioning
confidence: 98%
“…Antibiotics are not the only determinant of the success of H. pylori eradication therapy but host‐related factors also affect the eradication rate of any given therapy [9–11]. H. pylori creates a microenvironment to protect itself from gastric acid and host defense systems, and increases oxidative stress in areas it colonizes [2].…”
Section: Discussionmentioning
confidence: 99%